2016
DOI: 10.1073/pnas.1604256113
|View full text |Cite
|
Sign up to set email alerts
|

IL2Rβ-dependent signals drive terminal exhaustion and suppress memory development during chronic viral infection

Abstract: Exhaustion of CD8+ T cells severely impedes the adaptive immune response to chronic viral infections. Despite major advances in our understanding of the molecular regulation of exhaustion, the cytokines that directly control this process during chronicity remain unknown. We demonstrate a direct impact of IL-2 and IL-15, two common gamma-chain-dependent cytokines, on CD8+ T-cell exhaustion. Common to both cytokine receptors, the IL-2 receptor β (IL2Rβ) chain is selectively maintained on CD8 + T cells during chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…To determine whether the FV-specific PD-1/SIRPα double-positive CD8 + T cells from chronically infected mice comprised a subset of cells with a distinct phenotype, the expression of additional markers was examined by flow cytometry. The PD-1 + SIRPα + CD8 + T cells from chronically infected mice also expressed high levels of the co-inhibitory receptors Tim3 and Lag3, CD95 (Fas), which leads to apoptosis upon ligand binding, and IL-2Rβ chain (CD122), which helps drive a PD-1 hi phenotype 36 (Fig. 3a–d).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the FV-specific PD-1/SIRPα double-positive CD8 + T cells from chronically infected mice comprised a subset of cells with a distinct phenotype, the expression of additional markers was examined by flow cytometry. The PD-1 + SIRPα + CD8 + T cells from chronically infected mice also expressed high levels of the co-inhibitory receptors Tim3 and Lag3, CD95 (Fas), which leads to apoptosis upon ligand binding, and IL-2Rβ chain (CD122), which helps drive a PD-1 hi phenotype 36 (Fig. 3a–d).…”
Section: Resultsmentioning
confidence: 99%
“…The in vivo persistence and activation of adoptively transferred T cells is usually maintained by IL-2 infusion, but with IL-15 as exogenous supplement or as transgene expressed, preclinical mouse studies demonstrated an enhanced antitumor capacity of CD8+T cells compared with IL-2 [83]. Recent studies have shown that IL-2 and IL-15 both triggered CD8+ T cell exhaustion by similarly inducing the expression of inhibitory receptor in vivo, particularly 2B4 and TIM-3, and selective abrogation of their common IL-2Rβchain could retain the inhibitory receptor induction [84]. In breast cancer, IL-15 provoked higher proliferation and IFNγ production of tumor-infiltrating CD8+ T cells than IL-2, and these strong but short-lived response could be diminished by the subsequently upregulated TIM-3 [85].…”
Section: Immunomodulation Of T and Nk Cells In The Tumor Microenvironmentioning
confidence: 99%
“…CD122 (IL-2Rβ), a receptor shared by IL-2 and IL-15, becomes upregulated as exhaustion develops which correlates with the emergence of impaired functionality and increased PD-1 expression. Deletion of CD122 lessens exhaustion and increases functionality, implying that the integration of IL-2 and IL-15 signals influences the ontogeny and fates of exhausted CD8 T cells [ 191 ]. Although the expression of CD122 is prolonged on LCMV-specific CD8 T cells during chronic LCMV infection when compared to parallel populations in acutely infects hosts, expression on exhausted cells does eventually subside [ 59 , 191 ].…”
Section: Extrinsic Drivers Of T Cell Exhaustionmentioning
confidence: 99%